Wetland buffer zones for nitrogen and phosphorus retention: Impacts of soil type, hydrology and vegetation - Walton, Craig R.; Zak, Dominik; Audet, Joachim; Petersen, Rasmus Jes; Lange, Jelena; Oehmke, Claudia; Wichtmann, Wendelin; Kreyling, Jürgen; Grygoruk, Mateusz; Jabłońska, Ewa; Kotowski, Wiktor; Wiśniewska, Marta M.; et al. (The Science of the total environment, 2020)
Wetland buffer zones (WBZs) are riparian areas that form a transition between terrestrial and aquatic environments and are well-known to remove agricultural water pollutants such as nitrogen (N) and phosphorus (P). This review attempts to merge and compare data on the nutrient load, nutrient loss and nutrient removal and/or retention from multiple studies of various WBZs termed as riparian mineral soil wetlands, groundwater-charged peatlands (i.e. fens) and floodplains. Two different soil types (‘organic’ and ‘mineral’), four different main water sources (‘groundwater’, ‘precipitation’, ‘surface runoff/drain discharge’, and ‘river inundation’) and three different vegetation classes (‘arboraceous’, ‘herbaceous’ and ‘aerenchymous’) were considered separately for data analysis. The studied WBZs are situated within the temperate and continental climatic regions that are commonly found in northern-central Europe, northern USA and Canada. Surprisingly, only weak differences for the nutrient removal/retention capability were found if the three WBZ types were directly compared. The results of our study reveal that for example the nitrate retention efficiency of organic soils (53 ± 28%; mean ± sd) is only slightly higher than that of mineral soils (50 ± 32%). Variance in load had a stronger influence than soil type on the N retention in WBZs. However, organic soils in fens tend to be sources of dissolved organic N and soluble reactive P, particularly when the fens have become degraded due to drainage and past agricultural usage. The detailed consideration of water sources indicated that average nitrate removal efficiencies were highest for ground water (76 ± 25%) and lowest for river water (35 ± 24%). No significant pattern for P retention emerged; however, the highest absolute removal appeared if the P source was river water. The harvesting of vegetation will minimise potential P loss from rewetted WBZs and plant biomass yield may promote circular economy value chains and provide compensation to land owners for restored land now unsuitable for conventional farming. [Display omitted] •The efficiency of wetland buffer zones for nutrient retention was reviewed.•Organic and mineral soils as nutrient filters or sources were compared.•Processes driving phosphorus and nitrogen fluxes were described.•The indirect and direct impact of vegetation were unraveled.•Implications for wetland restoration and open research questions were specified.